The mTOR/Akt pathway is involved in regulating astrocyte growth and GLT-1 expression during cerebral ischemia-reperfusion - Qiuling Li; Yiwen Yu; Huan Deng; Biao Li; Hao Zhao; Dong Lei; Mi Li; Shansha Xie; Jingmei Yu; Yuping Zhao; Shubin Yin; YiFei Ji (PLoS ONE, 2026)
Stroke is one of the most prevalent causes of death and disability worldwide and places a heavy economic burden on families and society. High glutamate accumulation and subsequent excitotoxicity after ischemia and hypoxia are important pathogenetic mechanisms of brain injury after ischemic stroke. Glutamate transporter 1 (GLT-1) on astrocyte membranes is responsible for 90% of glutamate clearance. The involvement of the mTOR/Akt pathway in the upregulation of GLT-1 expression in astrocytes under oxygen-glucose deprivation and reoxygenation conditions has been demonstrated. Nevertheless, it is still unclear whether there is a negative feedback pathway from mTOR to Akt during cerebral ischemia/reperfusion (I/R). It has also not been elucidated whether the mTOR/Akt pathway is involved in the expression of astrocyte GLT-1 in cerebral I/R injury. In this study, we established a middle cerebral artery occlusion-reperfusion rat model to investigate the interactions and mechanisms of the mTOR/Akt cascade with GLT-1 under cerebral I/R conditions. These results provide evidence that brain I/R injury activates the mTOR/Akt pathway in the ischemic penumbra, increases astrocyte activation, and downregulates the expression of GLT-1. Inhibition of the mTOR pathway reversed GLT-1 downregulation and inhibited astrocyte activation by blocking the mTOR pathway, thereby attenuating neurological dysfunction, inflammatory response, and apoptosis caused by brain I/R injury. In contrast, inhibiting the Akt pathway did not provide neuroprotection, with no significant decrease in the number of astrocytes, inflammatory response, or apoptosis in the model group. Additionally, the inhibition downregulated GLT-1 expression and promoted the lengthening and thickening of astrocyte processes in cerebral ischemic rats. Thus, the mTOR/Akt cascade may be involved in regulating astrocyte growth and GLT-1 expression during brain I/R injury. Furthermore, inhibiting the mTOR pathway may mitigate apoptosis and the release of inflammatory factors, thereby fostering neuronal survival and safeguarding the central nervous system.